The Theory of Figurations of Norbert Elias and its Application to the Sociology of Recreational Sport among New Prestige Elites (Andamios, Revista de Investigación Social, 2015)
This paper shows how concepts such as civilizational process and figuration, both within the sociological theory of Norbert Elias, can be used to analyze the rising of new young professional elites in late capitalism. Our main interest in Elias’s notion of “sport curialization” led us to consider, both epistemologically and theoretically, the social construction of prestige among members of the “creative class”. This perspective also allowed us to analyze the theoretical richness of “double bind” relationships between citizens/outsiders which are useful to conceptualize the social link among young professionals hypermodern.
Keywords: Social figurations; recreational sport; lifestyles; Norbert Elias; creative class